Hairy vetch influence on nitrous oxide and nitrate leaching losses during corn growing seasons in reduced and no-till systems - Ashani Thilakarathne; Madhabi Tiwari; Oladapo Adeyemi; Amanda Weidhuner; Pawan Kumar; Gurbir Singh; Jon Schoonover; Karl Williard; Karla Gage; Amir Sadeghpour (Geoderma)
Shifting from reduced tillage (RT) to no-till (NT) often reduces phosphorus (P) runoff by minimizing soil erosion. However, it might increase nitrous oxide (N2O) emissions or nitrate-N (NO3-N) leaching. Including a legume cover crop such as hairy vetch (Vicia villosa L.) before corn (Zea mays L.) is a common practice among growers in the Midwest USA. However, the effects of hairy vetch following soybean (Glycine max L.) harvest on NO3-N leaching and N2O emissions during the following corn season in soil with clay and fragipans are less assessed. This study evaluated the influence of cover crop (hairy vetch vs. no-CC control) and tillage systems (NT vs. RT) when 179 kg ha−1 nitrogen (N) was applied at planting on (i) corn yield, N uptake, removal, and balance; (ii) N2O emissions and NO3-N leaching; (iii) yield-scaled N2O emissions and NO3-N leaching during two corn growing seasons. We also evaluated factors influencing N2O emissions and NO3-N leaching via principal component analysis. Corn grain yield was higher in RT (8.4 Mg ha−1) than NT (6.2 Mg ha−1), reflecting more available N in the soil in RT than NT, possibly due to the favorable aeration and increased soil temperature in deeper soil layers resulting from tillage. Hairy vetch increased corn grain yield and soil N. However, it led to higher losses of both N2O-N and NO3-N, indicating that increased corn grain yield, due to the hairy vetch’s N contribution, also resulted in higher N losses. Yield-scaled N2O-N emissions in NT-2019 (3696.4 g N2O-N Mg−1) were twofold higher than RT-2019 (1872.7 g N2O-N Mg−1) and almost fourfold higher than NT-2021 and RT-2021 indicating in a wet year like 2019, yield-scaled N2O-N emissions were higher in NT than RT. Principal component analysis indicated that NO3-N leaching was most correlated with soil N availability and corn grain yield (both positive correlations). In contrast, due to the continued presence of soil N, soil N2O-N fluxes were more driven by soil volumetric water content (VWC) with a positive correlation. We conclude that in soils with claypan and fragipans in humid climates, NT is not an effective strategy to decrease N2O-N fluxes. Hairy vetch benefits corn grain yield and supplements N but increases N loss through NO3-N leaching and N2O-N emissions.